CYTOGENETIC STUDIES OF LEUKEMIA INDUCED BY 6,8,12- AND 7,8,12-TRIMETHYLBENZ(A)ANTHRACENE - Sugiyama, Taketoshi (The Rockefeller University Press, 1970)
Cytogenetic studies on 64 rat leukemias induced with 7,8,12- and 6,8,12-trimethylbenz(a)anthracene were performed. Highly distinctive changes were found repeatedly in one special pair of chromosomes. 10 leukemias (15.6%) showed the presence of stemline(s) with trisomy of the largest telocentric chromosome (C-1 trisomy). Another chromosome abnormality, elongation of one of the pairs of the same chromosome (long C-1), was found in 5 leukemias (7.8%) as the predominant stemline and in 7 other cases as a small cell population. This chromosome abnormality, despite slight differences in their elongation rate, was defined as a new specific chromosome abnormality. Other chromosome abnormalities not related with C-1 chromosome were found in 8 cases (12.5%). The remaining 41 leukemias (64.1%) had the predominant stemline with normal karyotype. From this study it appears that three structurally different hydrocarbon carcinogens, 7,12-dimethylbenz(a)anthracene and 7,8,12- and 6,8,12-trimethylbenz(a)anthracene act on blood-forming cells by a common specific mechanism.